Factors influencing control of convulsive status epilepticus in children - Talukdar, Bibek; Bansal, Sumit; Jain, Rahul (Indian Journal of Child Health, 2019)
Background: Convulsive status epilepticus (CSE) is an important cause of morbidity and mortality in pediatrics. Objectives: The objectives of the study were to examine the influence of any clinical factor on control of CSE in children. Methods: Cases of CSE in the age group of 1 month–12 years, admitted to the emergency ward of a tertiary care hospital, over a period of 1 year, were studied, prospectively. Only those cases that were actively convulsing at arrival were enrolled. Difficult cases were shifted pediatric intensive care unit and were put on mechanical ventilator as needed. After initial stabilization, detailed case-work up and appropriate investigations to find the etiology were done. The data were analyzed statistically and p1 drug for controlling the convulsive episodes. Control was extremely difficult in 10 (20%) of the cases while 3 (6%) cases died. The time needed to control the episodes showed significant correlation with several clinical factors, namely focal seizure with impaired consciousness, multiple episodes of convulsion (discrete type), focal deficit, Glasgow Coma Scale score